2015
DOI: 10.1111/febs.13328
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of thermophilic limonene‐1,2‐epoxide hydrolases from hot spring metagenomic libraries

Abstract: The epoxide hydrolases (EHs) represent an attractive option for the synthesis of chiral epoxides and 1,2-diols which are valuable building blocks for the synthesis of several pharmaceutical compounds. A metagenomic approach has been used to identify two new members of the atypical EH limonene-1,2-epoxide hydrolase (LEH) family of enzymes. These two LEHs (Tomsk-LEH and CH55-LEH) show EH activities towards different epoxide substrates, differing in most cases from those previously identified for Rhodococcus eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 42 publications
(64 reference statements)
1
58
0
Order By: Relevance
“…Recently, we have discovered and characterized two novel LEHs (Tomsk‐LEH and CH55‐LEH) from hot‐springs metagenomic libraries . In agreement with their natural sources, both enzymes, which have been cloned and overexpressed in Escherichia coli , have higher optimal temperatures and apparent melting temperatures than Re ‐LEH.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, we have discovered and characterized two novel LEHs (Tomsk‐LEH and CH55‐LEH) from hot‐springs metagenomic libraries . In agreement with their natural sources, both enzymes, which have been cloned and overexpressed in Escherichia coli , have higher optimal temperatures and apparent melting temperatures than Re ‐LEH.…”
Section: Introductionmentioning
confidence: 84%
“…(Mardanov et al, 2011; Menzel et al, 2015). Many studies have also revealed the presence of genes encoding for enzymes of biotechnological interest, such as hydrolases, xylanases, proteases, galactosidases, and lipases (Ferrandi et al, 2015; Littlechild, 2015). Some studies focusing on the metagenomic analysis of hot springs located in India have reported Bacillus licheniformis (Mangrola et al, 2015), Bacillus megaterium, Bacillus sporothermodurans, Hydrogenobacter sp., Thermus thermophilus, Thermus brockianus (Bhatia et al, 2015), Clostridium bifermentans, Clostridium lituseburense (Ghelani et al, 2015), Opitutus terrae, Rhodococcus erythropolis , and Cellovibrio mixtus (Mehetre et al, 2016) as major bacterial genera.…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatic approach was used to identify the genes coding for these industrially important enzymes using the mesophilic Rhodococcus LEH as a search. The two new thermophilic LEHs have been cloned and over-expressed in E. coli and the resultant proteins characterised both biochemically and structurally [19]. The atomic coordinates and structure factors of the crystal structures obtained have been deposited in the PDB: 5AIF (Tomsk-LEH native structure), 5AIG (Tomsk-LEH valpromide complex), 5AIH (CH55-LEH native structure) and 5AII (CH55-LEH PEG complex).…”
Section: Epoxide Hydrolases From Extremophilic Metagenomesmentioning
confidence: 99%